Long-Term Clinical Outcome of Medial Shoulder Instability in a Dog Treated with Synthetic Implant, Cortical Button, and Interference Screw - Letesson, Julien; Crumière, Antonin; Goin, Bastien (VCOT Open, 2024)
Objective The objective of this study was to describe the surgical procedure and long-term outcome of traumatic medial shoulder instability in one dog treated with an ultra-high molecular weight polyethylene implant.A Fox Terrier had traumatic medial shoulder instability caused by the disruption of the subscapularis muscle and medial glenohumeral ligament. The joint was stabilized through a medial approach with an ultra-high molecular weight polyethylene implant secured on the glenoid by a cortical button and on the humerus by an interference screw. Postoperative and follow-up examinations were performed at 1, 2, 4.5 months, and 2.5 years.Results The patient bore weight after surgery and resumed normal gait after 2 months. Both the scapular and humeral tunnels had widened, essentially at their medial entrance, at 1 month postoperatively.Entrance diameter increased for 2 months and remained unchanged thereafter. An increase of 35 degrees in the abduction angle was observed in the long term at the 2.5-year control with minor osteoarthritis. No implant loosening, medial laxity, excessive abduction angle, inflammation, or septic reaction were observed.Conclusion The treatment of this case resulted in a satisfactory clinical outcome despite tunnel widening. This modified method using an interference screw could thus be considered as an alternative treatment of medial shoulder instability.
Keywords: dog; interference screw; medial glenohumeral ligament; medial shoulder instability; synthetic ligament reconstruction